Evaluating the static and dynamic modulus of elasticity of roller compacted rubbercrete using response surface methodology - Mohammed, B.S. (GEOMATE International Society, 2018)
In this study, response surface methodology (RSM) was used to evaluate the effect of partial replacement of fine aggregate with crumb rubber (CR), and the addition of nano silica (NS) by weight of cement in roller compacted concrete (RCC) pavement. Roller compacted rubbercrete (RCR) is used as the terminology for RCC where fine aggregate is partially replaced with crumb rubber. The experiments were designed and analysis executed using the historical data model type. After executing the experimental works, regression analysis was used to develop models for predicting the static and dynamic modulus of elasticity (MOE) of RCR. The RSM regression analysis showed that both static and dynamic MOE decreases with increase in CR replacement level, and increases with increment in addition of NS up to 2. Therefore CR increases the flexibility of RCR while NS increases its stiffness. The analysis of variance for the developed models showed that the static MOE of RCR can be predicted using cubic model type while the dynamic MOE can be predicted using quadratic model type, with all the models having high degree of correlation and was in agreement with the experimental data. Â© 2018, Int. J. of GEOMATE.